Efficacy of rituximab in refractory neuromyelitis optica. (June 2016) - Collongues, N; Brassat, D; Maillart, E; Labauge, P; Ouallet, JC; Carra-Dalliere, C; Moreau, T; Bourre, B; Papeix, C; Brochet, B; Audoin, B; Vukusic, S; et al.
Background: Despite a growing use of rituximab (RTX) in neuromyelitis optica (NMO), data are lacking in patients with refractory NMO (RNMO), defined as cases with at least one relapse during immunosuppressive therapy. Objective: The purpose of this study was to assess RTX as a maintenance therapy in RNMO. Methods: Out of a total of 305 NMO cases from a population-based cohort, 21 RNMO patients received RTX during a mean follow-up period of 31 months. Results: After RTX, 11 patients (52.3%) were relapse free, meaning that 47.7% were refractory to RTX. The mean annualized relapse rate decreased from 1.3 to 0.4 ( p <0.001) and median EDSS from 5 to 3 ( p =0.02). Body mass index (BMI) was predictive of EDSS worsening. Conclusions: RTX is an effective and well-tolerated treatment in RNMO. BMI could be a predictive factor for efficacy.